2022
DOI: 10.1007/s11071-022-07539-8
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and experimental studies of a vibro-impact capsule system driven by an external magnetic field

Abstract: This paper studies the electromagnetic field used for driving a vibro-impact capsule prototype for small bowel endoscopy. Mathematical models of the electromagnetic field and the capsule system are introduced, and analytical solution of the magnetic force applied on the capsule is derived and verified by experiment. The impact force between the inner mass of the capsule and the capsule body is also compared via numerical simulation and experimental testing. By comparing the capsule’s progressions under differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…It is worth noting that our robot has a peak velocity of 0.71 BL/s. Compared with the vibro-impact robots reported in the literature [ 28 , 30 , 51 , 52 , 53 ], the proposed robot has a clear advantage in its maximum velocity, which offers potential advantages in applications such as disaster search and rescue. In addition, it is noteworthy that when D = 1.6 mm, the robot exhibits noticeable backward locomotion near the impact frequency band, as highlighted in the red box in Figure 9 d. At 73 Hz, the maximum backward velocity of the robot reaches 16.9 mm/s.…”
Section: Robot Design and Characterizationmentioning
confidence: 99%
“…It is worth noting that our robot has a peak velocity of 0.71 BL/s. Compared with the vibro-impact robots reported in the literature [ 28 , 30 , 51 , 52 , 53 ], the proposed robot has a clear advantage in its maximum velocity, which offers potential advantages in applications such as disaster search and rescue. In addition, it is noteworthy that when D = 1.6 mm, the robot exhibits noticeable backward locomotion near the impact frequency band, as highlighted in the red box in Figure 9 d. At 73 Hz, the maximum backward velocity of the robot reaches 16.9 mm/s.…”
Section: Robot Design and Characterizationmentioning
confidence: 99%
“…The dynamic behaviour of the robot will be greatly affected by its complex environmental conditions, such as in the intestinal tract [20]. A miniaturised capsule prototype adopting external magnetic actuation was studied in [21]. Earlier studies on vibrational capsule [22] revealed that vibrations could be a potential means to reduce capsule-intestine resistances.…”
Section: Introductionmentioning
confidence: 99%
“…As a successive design adopted from [21], the main contributions of this work are summarised as follows. (1) The focus of this letter is to demonstrate the effectiveness of using vibro-impact method to drive the capsule robot for colonoscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MMAs adopt permanent magnets as movers, with compact structures and high power density. Zhang et al [20] introduced nonlinear models of the electromagnetic field and capsule system based on the Biot-Savart law and Charge model. Qin et al [21] established the dynamic model of a magnetic micromirror based on the Lorentz force on the mover.…”
Section: Introductionmentioning
confidence: 99%